Gifted Students: Exploring their Distribution According to the Type of Educational Institution - Navarro-Saldaña, Gracia (2022)
Background: Gifted students or students with academic potential need an enriching environment to achieve an outstanding performance. However, phenomena such as school segregation negatively affect the transformation of intellectual potential into academic talent. Objective: To compare the distribution of gifted students from the fifth grade of elementary school to the fourth year of high school in the Province of Concepción, Chile, coming from families of low, medium and high socioeconomic status, determined by the type of educational institution in which they study. Method: Six hundred fifty (650) students aged between 11 and 17 participated in the study and answered the Raven’s Progressive Matrices Test, which allowed the identification of the intellectual potential based on the cut-off score. Results: Statistically significant differences were found in the intellectual potential among students from public, subsidized private and fee-paying private educational institutions, as well as differences in the distribution of the intellectual potential relative to the students’ education level and their families’ socioeconomic status. Conclusions: When exploring the distribution of gifted students according to the type of educational institution, there was a higher concentration of those students in educational institutions with families of high socioeconomic status, and a lower concentration in educational institutions with families of low socioeconomic status. Authorship contribution The authors participated in the development of the article.